Incidence of dry eye after radiotherapy for head and neck tumours: a tertiary Care Hospital North West Rajasthan - Jain, Kalpna; Sagar, Vinod; Maharia, Sarita; Kumar, H. S. (International Journal of Research in Medical Sciences, 2021)
Background: Radiotherapy plays a critical role in the management of many patients with head-and-neck (H&N) cancer. To study the incidence of dry eye associated with radiotherapy and correlate them with dose of radiation. Methods: This Hospital based prospective study comprises of 100 patients of head and neck tumors who received radiotherapy by linear accelerator from 2015 to 2017. Ocular examination was done prior to the start of therapy, 1st follow up at 15th day of therapy, 2nd at last day of therapy (23-35 fraction), 3rd at 3 months after completion of therapy for side effects, 4th at 6 months, 5th at 12 month and 6th at 18 months after completion of therapy for assessing dry eye. Results: 59% patients developed dry eye. 44 patients received dose 45-55 Gy and out from these 13 (29.50%) patients developed dry eye, 40 patients received dose 56-65 Gy and out from these 33 (78.00%) patients developed dry eye and 16 patients received dose 66-70 Gy and out from these 13 (95.00%) patients developed dry eye. Conclusions: We concluded that the incidence of dry eye increased with increased total radiation dose. The current study suggests the importance of total dose as well as dose per fraction despite advancement of radiotherapy techniques and using protective mechanisms for eye complications developed.